Study on the RV Reducer based on Patent Map Technology - Chen Zhilan Chen Yunjie (Jixie chuandong)
Through the patent database of 5074 patent data, the patent map of technical progress of RV reducer in recent 74 years at home and abroad is studied. The patent map of the technical field of RV reducer is drawn by using international patent classification (IPC classification), patent map method and patent information data mining technology. From the global application number, application trend, the main application countries, the main competition institutions, patent distribution pattern, the main technology hot spot changes, key technology development areas and other aspects of a detailed analysis. The current situation of the research in the field of RV reducer is analyzed, and the development trend of the future technology is predicted, and the reference for the localization strategy layout of RV reducer is provided.